Impact of Diabetes Mellitus on Revascularization Success in Left Anterior Descending, Left Circumflex, and Right Coronary Arteries: A Retrospective Cohort Study - Shah, Tariq; Shah, Syed Muzammil; Khan, Fahad Raja; Rafi Ullah,; Muhammad, Abdul Wahab; Syed , Kashif ur Rahman (Indus Journal of Bioscience Research, 2024)
Background: Diabetes mellitus (DM) is a significant risk factor for cardiovascular disease and presents challenges in percutaneous coronary intervention (PCI), often leading to suboptimal revascularization outcomes. DM’s association with increased rates of restenosis and major adverse cardiac events (MACE) following PCI necessitates further investigation to guide management in this high-risk population. Objective: This study aimed to assess the impact of DM on revascularization success and secondary outcomes in patients undergoing PCI of the left anterior descending (LAD), left circumflex (LCX), and right coronary arteries (RCA). Methods: We conducted a retrospective cohort study at Hayatabad Medical Complex, Peshawar, analyzing clinical data from patients who underwent PCI between January 1, 2021, and December 31, 2021. Participants were categorized into diabetic (N=779) and non-diabetic (N=779) groups. Baseline characteristics, revascularization success rates, and secondary outcomes, including MACE and restenosis, were compared. Statistical analysis was performed using SPSS v27, with continuous variables analyzed via t-tests and categorical variables via chi-square or Fisher’s exact test as appropriate. Logistic regression was employed to adjust for potential confounders. Results: The revascularization success rate was significantly lower in diabetic patients (74.8%) compared to non-diabetic patients (83.2%) (p < 0.001). Diabetic patients also exhibited a higher incidence of MACE (12.9% vs. 6.9%) and restenosis (9.5% vs. 5.1%) compared to their non-diabetic counterparts (p < 0.001 for both outcomes). Increased BMI and LDL levels among diabetic patients were notable factors associated with adverse outcomes. Conclusion: Diabetes mellitus is associated with reduced revascularization success and increased adverse outcomes following PCI in LAD, LCX, and RCA arteries. These findings highlight the need for specialized therapeutic approaches and intensive follow-up in diabetic patients undergoing PCI to improve long-term outcomes.